Low serum adiponectin level is associated with metabolic syndrome and is an independent marker of peripheral arterial stiffness in hypertensive patients - Chen, Ming-Chun (Diabetol Metab Syndr, 2017)
BACKGROUND: Adiponectin has been implicated in metabolic syndrome (MetS) and arterial stiffness (AS). We aim to determine the relationship between serum adiponectin concentration as well as peripheral AS in hypertensive patients. METHODS: Fasting blood samples were obtained from 101 hypertensive patients. Brachial-ankle pulse wave velocity (baPWV) was measured with an automatic pulse wave analyzer. Serum adiponectin concentrations were determined by using an enzyme immunoassay kit. A baPWV >14.0 m/s was defined as high AS. RESULTS: MetS and high AS were present in 62.4 and 71.3% of the study population. Adiponectin was inversely associated with MetS and high AS (both P < 0.001). Serum higher high-density lipoprotein cholesterol (HDL-C) (P = 0.012), triglycerides (P = 0.001), C-reactive protein (P < 0.001), insulin (P = 0.027), body weight (P = 0.002), waist circumference (WC, P < 0.001), body mass index (P = 0.001) bilateral-baPWV (P < 0.001), systolic blood pressure (SBP, P < 0.001), diastolic blood pressure (DBP, P = 0.012), pulse pressure (P = 0.019), homeostasis model assessment of insulin resistance (HOMA1-IR (P = 0.026) and HOMA2-IR (P = 0.020)) and lower glomerular filtration rate (GFR, P = 0.029) were significantly associated with high AS. Multivariate logistic regression analysis of the factors significantly associated with AS revealed that adiponectin [odds ratio: 0.932, 95% confidence interval (CI) 0.881–0.985, P = 0.012], and SBP (odds ratio: 1.059, 95% CI 1.008–1.113, P = 0.022) were the independent predictors of arterial stiffness in hypertensive patients. Subgroup analysis revealed that SBP (odds ratio: 1.126, 95% CI 1.024–1.237, P = 0.014) and GFR (odds ratio: 0.858, 95% CI 0.739–0.996, P = 0.043) were the independent predictors of arterial stiffness in hypertensive patients without MetS; adiponectin (odds ratio: 0.909, 95% CI 0.931–0.996, P = 0.040) was the independent predictor of arterial stiffness in hypertensive patients with MetS. CONCLUSIONS: Hypoadiponectinemia has positive association with MetS and peripheral AS in hypertensive patients. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13098-017-0247-8) contains supplementary material, which is available to authorized users.